Liberalism as ideology essays in honour of Michael Freeden - Jackson, Ben, 1975-; Stears, Marc.; Freeden, Michael (Oxford : Oxford University Press, 2012)
Liberalism is the dominant ideology of our time, yet its character remains the subject of intense scholarly and political controversy. Inspired by the work of Michael Freeden, this text brings together an internationally-respected cast of scholars to debate liberalism and to redefine the very essence of what it is to be a liberal.
Festschrift for Michael Freeden.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Liberalism; Ideology; Liberalism -- History